Symbiotic development relationship between regional agricultural industry clusters and agricultural logistics - Wang, Wei; Cai, Aiting; Dai , Panqian (Transformations In Business & Economics, 2025)
Under the prevailing trend of coordinated industrial development, extending supply chains and strengthening industry linkages have emerged as critical pathways for upgrading modern agriculture. However, research into the dynamic symbiotic evolution mechanisms and optimization strategies of regional agricultural industry clusters and logistics systems remains insufficient, hindering the realization of high‐quality collaborative growth. To advance the co‐development of regional agricultural clusters and logistics, this study constructed a system dynamics model grounded in symbiosis theory. This model was applied to Jiangsu Province, China to investigate the feedback mechanisms and co‐evolutionary trajectories of the cluster–logistics symbiotic system. First, the symbiotic units, environmental factors, and interaction patterns were synthesized to develop causal loop and stock–flow diagrams. Second, scenario simulations were conducted following parameter calibration and validity testing against historical data. Finally, the effects of policy support, labor return, and transportation improvements on system performance were assessed. Results indicate that Jiangsu’s agricultural GDP will reach 1459.53 billion yuan by 2025. Elevating the policy support coefficient to 0.20 can increase cluster output value and logistics employment by approximately 3.92% and 3.50%, respectively. A 2% rise in labor supply yields a 17.44% increase in output value, and enhanced transportation accessibility boosts cluster output value and logistics capacity by 3.19% and 2.19%, respectively. Moreover, persistent rural labor outflow and logistics supply–demand imbalances are identified as principal constraints on collaborative development. These findings not only provide theoretical guidance for optimizing regional factor allocation and enhancing overall symbiotic system performance but also offer novel insights for advancing China’s agricultural modernization through “place‐based, differentiated strategies”.